The immune response to the novel coronavirus infection - Vyacheslav S. Fedorov (Eco-vector, 2021)
This review summarizes the current knowledge on the humoral and T-cell immunity to the novel coronavirus infection. A special attention is paid to the viral proteins that induce production of antibodies, different types of immunoglobulins and their role in the protection against the virus as well as to the duration of the humoral immune response. In addition, a concise analysis of the T-cell immunity status during COVID-19 and its input into the antiviral defense is presented. The collected data demonstrating preservation of both the humoral and T-cell immunity are urgently needed in the medical professionals' community for evidence-based decisions on the immunity monitoring, estimation of (re)vaccination time, as well as for knowing the factors that should be considered while choosing the most effective vaccine. Finally, several directions for the future research are pointed out